Response to third rubella vaccine dose. Issue 10 (3rd October 2018) - Siira, Lotta; Nøkleby, Hanne; Barlinn, Regine; Riise, Øystein R.; Aaberge, Ingeborg S.; Dudman, Susanne G.
ABSTRACT: Limited data exist on the immunogenicity of a third dose of the measles, mumps, and rubella vaccine (MMR). In this study, our aim was to evaluate the long-term rubella immunogenicity afforded by two childhood MMR doses of the Norwegian vaccination program in a cohort of conscripts and to determine the effect of an additional dose of MMR vaccine, in order to inform vaccination policy. Blood samples from Norwegian conscripts (n = 495) taken both before and eight months after administration of a dose of MMR vaccine were tested using an enzyme immunoassay to measure anti-rubella IgG. Concentrations <5 IU/mL were regarded as negative, 5.0-9.9 IU/mL as equivocal, and ≥10 IU/mL as positive. Overall, the seropositivity before vaccination was 84.6%, and 99.0% of the conscripts had anti-rubella IgG concentrations ≥5 IU/mL. The seropositivity after vaccination was 94.5%, and 99.8% of the conscripts had antibody concentrations ≥5 IU/mL. The geometrical mean IgG concentrations increased from 21.4 IU/mL before vaccination to 28.9 IU/mL after. Four out of five conscripts, with seronegative concentrations before administrations of an additional MMR dose, had equivocal or seropositive results following vaccination. The cohort of young adults in Norway, which was eligible for two childhood MMR doses, was protected against rubella, and efforts should be made to maintain high vaccine coverage to ensure immunity in the future. A third dose of MMR administered in early adulthood led to an increase in the antibody concentration in our cohort and seroconversion for the majority of seronegative persons.